2013
DOI: 10.1371/journal.pone.0070535
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to the WHO’s Healthy Diet Indicator and Overall Cancer Risk in the EPIC-NL Cohort

Abstract: BackgroundA healthy dietary pattern defined by international recommendations of the World Health Organisation (WHO) has been shown to reduce overall mortality risk. It is unknown whether this healthy dietary pattern is associated with overall cancer incidence.DesignIn total 35,355 men and women within the Dutch European Prospective Investigation into Cancer and Nutrition-cohort were followed for cancer occurrence. Diet was assessed through a validated food-frequency questionnaire. We computed a dietary score f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 37 publications
(41 reference statements)
1
41
0
Order By: Relevance
“…A summary of diet index scoring algorithms can be found in Table 1 (detailed summary in Supplemental Tables 3-6), as follows: 1) The HEI-2010 was developed by the USDA and the National Cancer Institute as an index of overall diet quality based on the 2010 US Dietary Guidelines for Americans (8,37,38); 2) The HDI is based on the international WHO dietary guidelines for the prevention of chronic diseases (43,44);…”
Section: Dietary Patternsmentioning
confidence: 99%
See 1 more Smart Citation
“…A summary of diet index scoring algorithms can be found in Table 1 (detailed summary in Supplemental Tables 3-6), as follows: 1) The HEI-2010 was developed by the USDA and the National Cancer Institute as an index of overall diet quality based on the 2010 US Dietary Guidelines for Americans (8,37,38); 2) The HDI is based on the international WHO dietary guidelines for the prevention of chronic diseases (43,44);…”
Section: Dietary Patternsmentioning
confidence: 99%
“…Each food group or nutrient guideline was assigned a score of 1 if intake met the guideline and 0 otherwise. The overall score was the sum of dichotomous variables (range: 0-7) (43,44). 5 The BSD has 9 components: fruit (apples, pears, and berries), vegetables (cabbage, roots, tomatoes, lettuce, and cucumber), fish, whole grains (barley, oats, and rye), low-fat milk, processed meat, restricting fat percentage, ratio of polyunsaturated to saturated and trans fat, and limiting alcohol.…”
mentioning
confidence: 99%
“…For the HDI an inverse association was seen with all-cause, CVD and cancer mortality (Huijbregts et al, 1997;Knoops et al, 2006), but not with breast cancer risk (Cade et al, 2011). In the EPIC-NL study no association was found between the HDI and cancer incidence (Berentzen et al, 2013) or CVD risk (Struijk et al, 2014c). These differences across diseases illustrate the need for an approach that summarizes the overall net relation between a dietary pattern and health.…”
Section: Discussionmentioning
confidence: 95%
“…The association between dietary patterns and single chronic diseases has been investigated before in EPIC-NL (Berentzen et al, 2013;Stricker et al, 2013;Waijers et al, 2006) and other populations (Mente et al, 2009;Romaguera et al, 2012;Sofi et al, 2010;Trichopoulou et al, 2005). The DHD-index was not associated with CVD risk and cancer (Struijk et al, 2014b,c); a Mediterranean-style diet was inversely associated with all-cause mortality (Knoops et al, 2004;Sofi et al, 2010;Trichopoulou et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation